2020
DOI: 10.1371/journal.ppat.1008612
|View full text |Cite
|
Sign up to set email alerts
|

If looks could kill: Fungal macroscopic morphology and virulence

Abstract: The complexity and diversity of microbial colony morphologies have contributed to the identification of pathogenic microbes for decades. Even as biomarker-based approaches are adopted for diagnosis of fungal infections, culture-based methods remain valuable for the identification of specific etiological agents and determination of antifungal susceptibility [1]. Thus, when obtainable, infectious organisms are observed as macroscopic colony biofilms in clinical settings. We define macroscopic morphologies (a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Another interesting observation was distinct morphotype displayed by P. funiculosum NCIM1228 on different growth media. Similar phenotype has been observed in Aspergillus species and has been suggested to impact its virulence characteristics [ 27 ]. Ability of a fungus to change its macroscopic morphotype in response to nutrient availability is quite intriguing.…”
Section: Discussionsupporting
confidence: 72%
“…Another interesting observation was distinct morphotype displayed by P. funiculosum NCIM1228 on different growth media. Similar phenotype has been observed in Aspergillus species and has been suggested to impact its virulence characteristics [ 27 ]. Ability of a fungus to change its macroscopic morphotype in response to nutrient availability is quite intriguing.…”
Section: Discussionsupporting
confidence: 72%
“…Penicillium species are globally distributed (Hassett et al 2019b), produce a suite of degradative enzymes (Park et al 2019), are commonly found in seafood (Park et al 2019), and can be abundant in the Arctic (Luo et al 2020). Our mortality experiments indicate that the presence of select P. chrysogenum strains can differentially reduce survival in copepods during a time span of weeks, consistent with variable virulence among strains of the same fungal species (Kowalski and Cramer 2020). Non-consumptive mortality of zooplankton in the Arctic may peak during winter months, as evidenced by sediment traps, which found Calanus carcasses to be the dominant component of sinking carbon outside of the spring bloom (Sampei et al 2012).…”
Section: Discussionsupporting
confidence: 57%
“…showed a similar hyphal growth rate and normal hyphal characteristics, but slightly different colony morphology. Since changes in colony morphology and growth rate can be due to biotic or environmental stresses (Morales et al, 2013;Liu et al, 2017;Orosz et al, 2018;Kowalski and Cramer, 2020), our observations imply that Cosmospora sp. could tolerate the negative effects of the substances secreted by P. noxius.…”
Section: Discussionmentioning
confidence: 79%